Interpenetrating networks in Zr–Cu–Al and Zr–Cu metallic glasses - Wang, Chang Chun. (2013)
The short-range order and medium-range order of ternary Zr–Cu–Al and binary Zr–Cu metallic glasses (MGs) have been investigated. When substituting a few percent of Al for Zr in the Zr–Cu alloy, the resultant ternary alloy exhibits more full icosahedra. Furthermore, the number of Zr icosahedral atoms increases significantly since Al-centred full icosahedra favours Zr as neighbour atoms. Additionally, the interconnecting networks in Zr–Cu–Al MG are enhanced significantly through intensive sharing frequencies between the full icosahedra. The reduction of isolated icosahedra in the ternary system lowers the atomic mobility and slows down the dynamics in the supercooled liquid region, which reduces theoretical cooling rate for the preparation of bulk MG.